1990
DOI: 10.2118/18387-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Aspects of Partitioning Tracer Tests for Residual Oil Saturation Determination With FIA-Based Laboratory Equipment

Abstract: Summary Partitioning tracer tests are used to determine residual oil saturation (ROS). At Koninklijke/Shell Laboratorium, Amsterdam, laboratory equipment based on the flow injection analysis (FIA) method has been constructed for rapid (within 2 hours) and accurate (better than 8%) determination of the equilibrium partition coefficient of tracers between crude oil and brine under simulated reservoir conditions. The apparatus makes possible investigation of the influence of all relevant paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Even for simple species, such as alkylphenols, the organic-aqueous phase partition process is complex (Bizek et al 1992), but the relatively greater affinity of phenol and the cresols for water compared to higher alkylphenol homologues is accurately reflected in the relative compositions of the oils and formation waters. While the actual water-oil partition coefficients will change with temperature, pressure, salinity and solution-gas content (Knaepen et al 1990), these initial results lend confidence to the idea that the Fig. 15.…”
Section: Evidence For Oil-water-rock Interactionmentioning
confidence: 74%
“…Even for simple species, such as alkylphenols, the organic-aqueous phase partition process is complex (Bizek et al 1992), but the relatively greater affinity of phenol and the cresols for water compared to higher alkylphenol homologues is accurately reflected in the relative compositions of the oils and formation waters. While the actual water-oil partition coefficients will change with temperature, pressure, salinity and solution-gas content (Knaepen et al 1990), these initial results lend confidence to the idea that the Fig. 15.…”
Section: Evidence For Oil-water-rock Interactionmentioning
confidence: 74%
“…However, some qualitative insights on the effects of these variables on partition coefficients may be evaluated from experiments conducted by Knaepen et al (1990). Their experiments determined the partition coefficients for pentanol-l and ethylacetate in isooctane/water or North Sea oil/water systems at different temperatures (22 to 150°C), water salinities (0 to lOwt% NaCl), and gas/oil ratios (0 to 230 v/v).…”
Section: Expulsion Timing and Mechanismsmentioning
confidence: 99%
“…Although partition coefficients for organic acids in water and pure hydrocarbons are available at 25°C and 1 atm (Leo et al 1971), partition coefficients for organic acids in water and petroleum are not available under reservoir conditions. The laboratory experimental study by Knaepen et al (1990) has shown that the partition coefficients for ethyl acetate in water and petroleum can be significantly different with increasing water salinity, dissolved gas content, and temperature. Future research using a similar experimental approach to determine partition coefficients for organic acids under reservoir conditions is needed.…”
Section: Laboratory Experimental Studiesmentioning
confidence: 99%